Political cycles and bank lending in Russia - Zuzana Fungáčová; Koen Schoors; Laura Solanko; Laurent Weill (Bank of Finland, Institute for Economies in Transition (BOFIT), 2020)
State-owned banks tend to increase lending before elections for the purpose of boosting the re-election odds of incumbent politicians. We employ monthly data on individual banks to study whether Russian banks increased their lending before presidential elections during 2004-2019, a period covering four presidential elections. In contrast to the literature, we find that both state-owned and private banks increased their lending before presidential elections. This result stands for all loans, as well as separately for firm and household loans. The pre-election lending surge is followed by a deterioration of loan quality the following year, indicating the lending increase was not driven by higher growth prospects or some positive economic shock. The effect is substantially greater for large banks and banks more involved in lending activities. Our main finding that all types of banks in Russia increase their lending before presidential elections supports the view that the authorities in an electoral autocracy like Russia can influence lending of both private and state-owned banks for political reasons.
URN:NBN:fi:bof-202003252052
Keywords: G21; P34; 330; bank; lending; politics; Russia